Felicidade e amizade na ética nicomaquéia - Rodriguez Fleitas, Horacio Francisco (My University, 2016)
Happiness (eudaimonia) and friendship (philia) are widely discussed themes in the work of Aristotle, however, are treated especially in his works on ethics and politics, especially in the Nicomachean Ethics. This dissertation analyzes the relationship and complementarity of these two issues in the Nicomachean Ethics and the research methodology for the composition of this study is bibliographic, providing itself as basic theoretical background to the investigations, considerations and arguments of Aristotle in the above cited work, specifically in the Books I, II and X dealing with the theme of happiness and books VIII and IX, which address the theme of friendship. In addition to the contributions arising from enlightening analysis of commentators and interpreters of the research topics and the universe of Aristotle's work.The survey results support the conclusion that Aristotle argues that the society of virtuous men, established in friendship is conducive to promoting the achievement of the purpose of man's existence, which is happiness. These results lead in conclusion, the recognition of the interrelationship and complementarity of the concepts of happiness and perfect friendship, forming a substantial dyad, both for the realization of existence as to the completeness, excellence, of human life.
A felicidade (eudaimonia) e a amizade (philia) são temas amplamente abordados na obra de Aristóteles, não obstante, são tratados com destaque em suas obras sobre a ética e a política, especialmente na Ética a Nicômacos. A presente dissertação analisa a relação e complementariedade destes dois temas na Ética Nicomaquéia e a metodologia de investigação para a composição deste estudo é a bibliográfica, dispondo-se como aporte teórico basilar as investigações, considerações e argumentações de Aristóteles na obra acima citada, especificamente nos Livros I, II e X que tratam da temática da felicidade e nos Livros VIII e IX, que abordam o tema da amizade. Além das contribuições surgidas das análises elucidativas de comentaristas e intérpretes dos temas investigados e do universo da obra aristotélica. Os resultados da pesquisa permitem considerar que Aristóteles pondera que o convívio dos homens virtuosos, estabelecido na amizade, é propício para promover a consecução da finalidade da existência do homem, que é a felicidade. Estes resultados conduzem, como conclusão, ao reconhecimento da inter-relação e complementariedade dos conceitos de felicidade e amizade perfeita, conformando uma díade substancial, tanto para a realização da existência quanto para a completude, na excelência, da vida dos homens.
Keywords: Aristóteles; Felicidade; Amizade; Ética; Virtudes; Happiness; Friendship; Ethics; Virtues